Features of the expression of fibroblast growth factor in patients with idiopathic atrial fibrillation and verified myocarditis. (14th October 2021) - Gusakova, A; Suslova, T.E; Shelemehov, A.E; Rogovskaya, Y.V; Batalov, R.E
Abstract: Introduction: Myocarditis and inflammatory changes in the myocardium can be one of the causes of the development and progression of atrial fibrillation (AF). The biomarker FGFβ is involved in the processes of angiogenesis, repair of heart tissues and stimulates fibroblasts. Purpose: To assess the dynamics and to identify the relationship of fibroblast growth factor (FGFβ) expression and myocardial inflammatory diseases revealed by the results of histological examination of endomyocardial biopsy in patients with various forms of idiopathic AF. Methods: Subjects were 40 patients (41.0±9.2 y.o.) with idiopathic AF, the arrhythmic history constituted 4.9±3.9 years. The patients were divided into 3 groups: 1–with paroxysmal AF (n=15), 2–persistent (n=12), 3–long-term persistent (n=13) depending on the form of AF. All patients underwent radiofrequency ablation (RFA) of the pulmonary veins and endomyocardial byopsy with histologic and immunohistochemical studies. In 1st group active lymphocytic myocarditis (ALM) were found in 40% patients (n=6); in 2d and 3d groups – 66.7% (n=8 in each gr.). All other patients showed signs of lymphocytic infiltration (LI). The serum levels of FGFβ determined all patients in prior to intervention (T1) and in 6 months after RFA (T2). Results: Comparative analysis showed, in patients with morphologically verified ALM, the FGFb levels in 6 months after RFA in 1st gr. was significantly higher than in 3d gr. (p=0.036). In patients gr.1 with ALM the levels of FGFb was higher (at stages T1 and T2) than in patients with LI (p=0.055 and p=0.06, respectively). In 1st gr., a positive association between the levels of FGFb (T1) and the degree of activity of inflammatory processes caused in 6 months after RFA (R=0.95 p=0.005) were identified. In 1st gr., the relationship between the degree of activity of inflammatory processes and fibrotic changes (R=−0.77 p=0.009) and an association of FGFb with the value of cardiac ejection fraction was obtained (R=0.90 p=0.037). In 2d gr., strong correlations of FGFb with the degree of activity of inflammatory processes (R=0.79 p=0.019) and ejection fraction (RT1=0.73 p=0.039, RT2=0.96 p=0.0002) were revealed. In 3d gr., the FGFb levels was significantly higher in patients with LI than with ALM (14.74 [13.28; 14.80] and 6.92 [5.65; 9.90] pg/ml, respectively; p=0.048). In 3d gr., the severity of fibrotic changes was associated with FGFb expression (RT1=−0.73 p=0.041, RT2=−0.85 p=0.008). Conclusion: The relationships of FGFb with the degree of activity of inflammatory processes in groups with paroxysmal and persistent AF were revealed. In patients with active lymphocytic myocarditis, the FGFb level was significantly higher in paroxysmal AF than in long-term persistent AF. Our study showed, increased expression of FGFb is associated with inflammatory processes of active lymphocytic myocarditis, and may be due to intense proliferation and differentiation of fibroblasts in paroxysmal AF. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Cardiology Research Institute, Tomsk NRMC